Implementation of Marketing Information System on Android-Based Agriculture Sector: A Short Review - Inayatul Rizqiana; Masduki Asbari; Dewiana Novitasari (Journal Of Communication Education, 2023)
This paper is designed based on the material entitled marketing information system while the title of the discussion explains the android-based agricultural sector, concerning the paper entitled marketing information system with the role of the agricultural sector in economic development in Indonesia due to the lack of the agricultural sector in the food sector. The method used is the black box method, for the writing method the author uses qualitative methods. The qualitative method is a method that focuses on in-depth observations with references from scholars. The results of the black box method are very beneficial for the community, especially people who are still dependent on the sector.